2022
DOI: 10.1206/0003-0090.457.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Craniodental Morphology and Phylogeny of Marsupials

Abstract: The current literature on marsupial phylogenetics includes numerous studies based on analyses of morphological data with relatively limited sampling of Recent and fossil taxa, and many studies based on analyses of molecular data that include a dense sampling of Recent taxa, but relatively few that combine both data types. Another dichotomy in the 9 2021) belonging to seven clades that are currently ranked as orders in the Linnean hierarchy (Table 1; Aplin and Archer, 1987;Wilson and Reeder, 2005;Burgin et al.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 784 publications
2
75
0
Order By: Relevance
“…The parsimony-based 50% majority-consensus tree of discrete data outperformed most GMM-based analyses. However, as with the GMM-based trees, discrete-based trees derived from the basicranial dataset had substantially lower similarity to the reference tree, whereas the dataset of all characters (the full matrix from [36]) resulted in a markedly better-performing tree.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parsimony-based 50% majority-consensus tree of discrete data outperformed most GMM-based analyses. However, as with the GMM-based trees, discrete-based trees derived from the basicranial dataset had substantially lower similarity to the reference tree, whereas the dataset of all characters (the full matrix from [36]) resulted in a markedly better-performing tree.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the performance of our GMM-based trees with trees based on discrete characters, we also produced phylogenetic trees based on the discrete morphological character dataset of [36]. We partitioned this dataset into: (1) a dataset comprising basicranial characters, excluding four characters relating to the ossicles, resulting in 38 characters that correspond to characters 47–56 and 67–88 of the original list of [36]; (2) a dataset comprising characters from the remainder of the cranium, resulting in 53 characters that correspond to characters 1–46 and 89–95 of the original list of [36]; (3) a dataset that corresponds to the original, ‘full’ 180 character dataset of [36], which comprises cranial, mandibular and dental characters. These discrete datasets comprised 144 taxa [36], but only 45 of these were comparable (even when using congenerics) to the 57 in the GMM dataset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this same analysis, Bobbschaefferia stands out as a plesiomorphic sister group to the rest of the Polydolopimorphia. Recently, Beck (2017) tentatively proposed the existence of a “staggered” lower incisor in specimen MNRJ 2880-V of Epidolops ameghinoi de Paula Couto, 1952 (de Paula Couto, 1952b) on the basis of a single alveolar space (see Beck et al, 2022 for a discussion on the staggered condition among marsupials). On the contrary, we suggest that the condition of Epidolops resembles more that of Bobbschaefferia as well as that of other basal polydolopimorphians; that is, that the lower incisors are aligned rather than one of them being staggered.…”
Section: Resultsmentioning
confidence: 99%
“…They are thus readily distinguishable from one another. Their last common ancestor probably existed in the later Miocene about 6-8 million years ago (Westerman et al 2016;Kealy and Beck 2017;García-Navas et al 2020;Beck et al 2022), enough time for each to have developed distinct phenotypes in adapting to their arid habitats. Woolley et al (2007) showed that penis structure of the long-tailed dunnart (Form 9) differs from that of all other species of Sminthopsis.…”
Section: Discussionmentioning
confidence: 99%